Supervisory participative behavior and employees' job satisfaction, behavior and work performance: a longitudinal quasi-experiment - Zakaria Ismail,; Abd. Aziz Kadir, (Penerbit Universiti Kebangsaan Malaysia, 1989)
This study attempts to investigate the effects of supervisory participative behavior on employee attitudes, behaizor and work performance using a quasz-experimental design in field setting. One hundred and twenty eight employees from a Malaysian Government agency were selected and randomly assigned into experimental and control groups. The results indicated, firstly, that supervisory participative behavior did not have significant effects on employees' job satisfaction. Secondly, although the supervisory participative behavior was found to have significant effects on the employees' work behavior (absenteeism and intent-to-stay) at posttest 1 , the effects seemed to diminish at posttest 2. Finally, whilst quantity of work was strongly influenced by supervisory participative behavior, quality of work, however, was not.